Прогнозування успішності інтродукції видів роду Cypripedium L. (Orchidaceae) - Sobko, V.G.; Reshetjuk, О.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
The prognosis of the successful introduction of plants of genus Cypripedium L. are based on systematic, phyllogenetic, geographical and ecological-cenotic analysis of the investigated taxon.